2020
DOI: 10.1016/j.frl.2019.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The development of Bitcoin futures: Exploring the interactions between cryptocurrency derivatives

Abstract: This is a repository copy of The development of Bitcoin futures : exploring the interactions between cryptocurrency derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 26 publications
(15 reference statements)
3
44
0
Order By: Relevance
“…Gox Bitcoin exchange; a notable by-product of their research is the finding that suspicious trading on one exchange led to equal price changes on other exchanges, suggesting traders can effectively engage in arbitrage activities across exchanges. Similarly, signs of efficiency are detected in Akyildirim et al (2019) who investigate pricing of Bitcoin futures on traditional exchanges-Chicago Mercantile Exchange (CME) and the Chicago Board Options Exchange (CBOE). Importantly, in their study information flows and price discovery go from futures to spot markets, in contrast to previous results for traditional assets; a likely explanation is the difference in the type of traders at cryptoexchanges (that determine the spot price) and both CME and CBOE.…”
Section: Discussionmentioning
confidence: 96%
“…Gox Bitcoin exchange; a notable by-product of their research is the finding that suspicious trading on one exchange led to equal price changes on other exchanges, suggesting traders can effectively engage in arbitrage activities across exchanges. Similarly, signs of efficiency are detected in Akyildirim et al (2019) who investigate pricing of Bitcoin futures on traditional exchanges-Chicago Mercantile Exchange (CME) and the Chicago Board Options Exchange (CBOE). Importantly, in their study information flows and price discovery go from futures to spot markets, in contrast to previous results for traditional assets; a likely explanation is the difference in the type of traders at cryptoexchanges (that determine the spot price) and both CME and CBOE.…”
Section: Discussionmentioning
confidence: 96%
“… Kapar and Olmo [2019] use the Coindesk Bitcoin USD Price Index as the spot price. Akyildirim, Corbet, Katsiampa, Kellard, and Sensoy [2019] find that Bitcoin futures dominate price discovery relative to spot markets using the information share methodology of Hasbrouck [1995] , Gonzalo and Granger [1995] , Yan and Zivot [2010] and Hauptfleisch, Putniņš, and Lucey [2016] . Baur and Dimpfl [2019] also investigate the price discovery of Bitcoin using the information share methodology of Hasbrouck [1995] and Gonzalo and Granger [1995] at the five-minute frequency for intradaily data.…”
Section: Introductionmentioning
confidence: 93%
“…In their paper, the transaction price of Bitstamp is used as the Bitcoin spot price in the analysis for the two futures markets. Although Corbet et al [2018] , Kapar and Olmo [2019] , Akyildirim et al [2019] and Baur and Dimpfl [2019] use the same price discovery measures of Hasbrouck [1995] and Gonzalo and Granger [1995] , they produce different results. Not only are the future contracts of the CBOE and CME different, but the underlying spot prices used are also different, see Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Further, Anand, Gatchev, Madureira, Pirinsky, and Underwood (2011) identified the role of geographic influence, while Nimalendran and Ray (2014) showed that algorithmic trades for less liquid stocks are correlated with higher spreads and price impact, as well as contemporaneous trading on the lit venues. In recent research relating to rapidly growing cryptocurrency markets, price discovery and information flows have been analysed using Bitcoin ( Akyildirim, Corbet, Katsiampa, Kellard, & Sensoy, 2020 ; Brandvold, Molnár, Vagstad, & Andreas Valstad, 2015 ; Corbet, Lucey, Peat, & Vigne, 2018 ; Katsiampa, Corbet, & Lucey, 2019a ; Katsiampa, Corbet, & Lucey, 2019b ) where Mt.Gox and BTC-e were identified to be market leaders with the highest information share and Bitcoin futures dominate price discovery relative to spot markets.…”
Section: Previous Literaturementioning
confidence: 99%